2016
DOI: 10.5506/aphyspolbsupp.9.515
|View full text |Cite
|
Sign up to set email alerts
|

QCD with Chiral Chemical Potential: Models Versus Lattice

Abstract: An emergence of local spatial parity breaking (LPB) in central heavyion collisions (HIC) at high energies is discussed. The QCD phenomenology of LPB in the fireball is induced by a difference between the number densities of right-and left-handed chiral fermions which is triggered by a chiral (axial) chemical potential. For the description of peculiarities of LPB, a number of QCD-inspired models are considered and confronted to certain lattice results. In particular, from the meson effective Lagrangian, it is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…To increase predictability, we extend the vacuum Chiral Lagrangians [12,13] with phenomenological low-energy structural constants taking into account the chiral medium in the fireball with a chiral imbalance. It is shown that σ-model parametrization of [11] fits well the pion phenomenology at low energies as derived from ChPT.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…To increase predictability, we extend the vacuum Chiral Lagrangians [12,13] with phenomenological low-energy structural constants taking into account the chiral medium in the fireball with a chiral imbalance. It is shown that σ-model parametrization of [11] fits well the pion phenomenology at low energies as derived from ChPT.…”
Section: Introductionmentioning
confidence: 66%
“…• [14], that at higher energies exotic decays of isoscalar mesons into three pions arise due to mixing of π and a 0 meson states in the presence of chiral imbalance. It was shown [7,11,14] that a wider class of direct parity breaking at higher energies, in the framework of linear sigma model with isotriplet scalar (a 0 ) and pseudoscalar (pions) mesons their mixing arises with generation of ππ and πππ decays of heavier scalar state. As well the independent check of our estimates could be done by lattice computation (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the previous conference "eQCD2016" [17] we declared also a manifestation for LPB in the presence of chiral imbalance in the sector of ρ and ω vector mesons. It turns out [10] that the spectrum of massive vector mesons splits into three components with different polarizations having different effective masses m 2 V,+ < m 2 V,L < m 2 V,− .…”
Section: Discussionmentioning
confidence: 99%
“…The transition of the quark-gluon medium characteristics to a hadron matter reckons on the quark-hadron continuity [10] after hadronization of quark-gluon plasma. The behavior of various spectral characteristics for light scalar and pseudoscalar (σ, π a , a a 0 ) -mesons by means of a QCD-motivated σ-model Lagrangian was recently derived for SU L (2) × SU R (2) flavor symmetry including an isosinglet chiral chemi-cal potential [11]. The structural constants of the σ-model Lagrangian were taken as input parameters suitable to describe the light meson properties in a chiral medium.…”
Section: Introductionmentioning
confidence: 99%